Super cavity model with the coupling reaction of slender body motion and water flow - Ha, Tran Thu; Thuyen, Nguyen Duc; Dung, Nguyen Thai; Hai, Duong Ngoc (Vietnam Journal of Mechanics, 2018)
On the imperfect water entry, a high-speed slender body moving in the forward direction, rotates inside the cavity. The body's motion makes super cavity phenomena in the water flow. The water velocity and pressure fields interact during the body's motion. In this paper, the coupling simulation model is a combination of two sub-models: In the first sub-model, the motion of slender body running very fast underwater is simulated. The equation system of this sub-model is solved by Runge-Kutta method; In the second sub-model, the water flow and pressure field under reaction of very fast slender body motion are simulated by CFD model. The simulation results of this coupled model are compared with experiments based on magnitudes of velocity U by x0 direction and error percents for cavity diameter and length.